Deep Learning Techniques in Acute Lymphoblastic Leukemia Classification : State-of-the-Art Review - sama M. A. Yousif; Eltyeb Elsamani Abdelgabar Elsamani; Ibrahim Rizqallah Alzahrani; Adil Mahmoud Mohamed Mahmoud (White Nile Journal for Studies and Research, 2025)
Diagnosing acute lymphoblastic leukemia (ALL) is a major challenge in medical practice, as traditional methods يعد تشخيص اللوكيميا اللمفاوية الحادة (ALL) تحدياً كبيراً في الممارسة الطبية، حيث إن الطرق التقليدية مثل الفحص المجهري والتحاليل الجزيئية تفتقر إلى الدقة العالية وتستهلك وقتاً وجهداً كبيرين، في السنوات الأخيرة أسهمت تقنيات التعلم العميق، وبخاصة الشبكات العصبية الالتفافية (CNN) في إحداث نقلة نوعية في تحليل صور الدم وتشخيص المرض. تهدف هذه الدراسة إلى إجراء مراجعة منهجية للأبحاث المنشورة بين عامي 2015 و 2023 في قواعد بيانات متخصصة مثل PubMed و IEEE Xplore و Scopus و Web of Science مع التركيز على النماذج المعتمدة على CNN النماذج الهجينة (CNN-LSTM/GRU). وأساليب التعلم بالنقل والتجميع، تم تصنيف الدراسات ومقارنتها وفق معايير الأداء الشائعة مثل الدقة، الاسترجاع، المعامل التوافقي F1 ومساحة المنحنى ROC-AUC، وتبرز المراجعة أن دمج الـ CNN مع وحدات GRU يشكل تحسيناً واعداً مقارنة بالنماذج التقليدية لما يجمعه من قدرة عالية على استخراج السمات المكانية وكفاءة في معالجة العلاقات التسلسلية، مع تقليل الكلفة الحسابية مقارنة بـ LSTM، وتظهر النتائج أن هذا التوجه يوفر دقة وموثوقية أعلى. خصوصاً عند التعامل مع بيانات محدودة أو غير متوازنة، مما يجعله مناسباً للتطبيقات السريرية وللتنفيذ في بيئات الحوسبة محدودة الموارد (Edge (AI)uch as microscopy and molecular analysis lack high accuracy and are time-consuming and labor-intensive. In recent years, deep learning techniques, particularly convolutional neural networks (CNNs), have revolutionized blood image analysis and disease diagnosis. This study aims to conduct a systematic review of research published between 2015 and 2023 in specialized databases such as PubMed, IEEE Xplore, Scopus, and Web of Science, focusing on CNN-based models, hybrid models (CNN LSTM/GRU), and transfer learning and clustering methods. Studies were ranked and compared according to common performance metrics such as precision, recall, F1 coefficient, and ROC-AUC. The review highlights that combining CNNs with GRUs represents a promising improvement over traditional models, combining superior spatial feature extraction capabilities and efficient sequential relationship processing, while reducing computational cost compared to LSTMs. The results demonstrate that this approach provides higher accuracy and reliability, especially when dealing with limited or imbalanced data, making it suitable for clinical applications and implementation in resource-constrained computing environments (Edge AI). Keywords: Acute Lymphoblastic Leukemia, Convolutional Neural Networks, Transfer Learning, Recurrent Neural Networks, Classification.